Modifikasi Kemasan Dengan Menggunakan Ziplock di P4S X Kabupaten Kulon Progo - Khairunnisa, Khairunnisa; Munambar, Siwitri; Rimartin, Geraldo Adinugra (Jurnal Ilmiah Manajemen, Bisnis dan Kewirausahaan, 2025)
UMKM have a strategic role in the national economy, but the competitiveness of their products is still weak due to unattractive packaging that does not meet standards. This study aims to modify the packaging of Ginger Honey Powder Drink products at P4S X Kulon Progo Regency to make them more functional and visually attractive. The method used is mixed methods with a quasi-experimental design in the form of a pre-test and post-test without a control group. Data collection techniques include interviews, FGDs, observations, and questionnaires to 50 consumers. The results show that the use of ziplock packaging improves consumer perceptions in terms of visual aspects, functionality, and overall satisfaction. The average perception score increased significantly after the packaging modification was carried out. This study emphasizes the importance of packaging innovation based on consumer preferences as a strategy to increase the selling value of UMKM products.